A long and winding road: Towards a palethnograpic interpretation of the middle-Gravettian site of la Picardie (Indre-et-Loire, France). (30th December 2018) - Klaric, Laurent; Bertran, Pascal; Dumarçay, Gaëlle; Liard, Morgane
Abstract: After nine years of excavation (1998–2008) the site of La Picardie has delivered a significant lithic collection (more than 13, 000 artefacts coordinated) chronologically related to the "Raysse burin" phase of the Gravettian (second phase of Middle Gravettian ca. 25–23 ky BP uncal.). The study of the lithic material has provided several important results, including the chronological attribution of the site, the description of a new type of retouched bladelet, and the reconstruction of the flint knapping process for blade and bladelet production on site. The palethnographic study and interpretation of the site have, however, not been discussed to date. In spite of some taphonomic issues the coalescence of different studies has allowed us to further our understanding of the site, notably via the functional analysis of stone tools, the evaluation of different skill levels in flint-knapping, the vertical and horizontal distributions of artefacts and tools, and finally the study of the different organised "structures" made of limestones blocks. Using several examples we will describe in a step by step manner the various elements that helped us to rebuild the probable function(s) of the site and propose a first palethnographic assessment.